Analisis Kekebalan Hukum Terhadap Pejabat Negara Dalam Misi Khusus Pada Kasus Ehud Barak Menurut Konvensi New York 1969 - Muhammad Yogi Nofran; Azifah Syaqila Ravadina Suhendra; M. Azzah Rozanda (GLOBAL SCIENTS PUBLISHER, 2026)
The legal immunity of state officials in special missions remains an unresolved issue in international diplomatic law. The Convention on Special Missions (New York, 1969) provides a normative basis for such immunity, yet its application in practice remains contentious, particularly when confronted with demands for legal accountability for alleged serious violations. This study examines the normative framework of the 1969 New York Convention and analyzes its application to the case of Ehud Barak, former Prime Minister and former Minister of Defense of Israel, who faced legal claims in the context of his official visit to a third state. Employing normative legal research methods through statutory, case, and comparative approaches, this study finds: first, special mission immunity possesses characteristics that are fundamentally distinct from permanent diplomatic immunity and is operative only upon the cumulative fulfillment of conditions established by the Convention; second, the application of immunity in Barak's case depends on verification of three normative conditions, namely the existence of an official mandate from the sending state, the consent of the receiving state, and the official status at the time of the visit. This study concludes that the ambiguity of the 1969 New York Convention regarding verification procedures for special missions contributes to legal uncertainty in international practice and underscores the need for reform of that instrument.